HUBUNGAN TANGGAPAN DAN SIKAP WARGA KOTA MADIUN TERHADAP MEMBAYAR ZAKAT/ JIZYAH SEBAGAI SUMBER APBN/APBD - Muhayati, Siti; Triningtyas, Diana Ariswanti; Muwarni, Juli (Jurnal Counsellia, 2015)
Between Budget and Budget State Local Income in equality especially lower budget from the budget, and 50%-60% Budget spent for paying employees the reasons is the lack of participation of citizens to fund the management of the state by paying the zakat (Muslim) jizyah (non-Muslim). The purpose of this study was to determine the response and attitude of the towns people Madiun to pay Zakat/jizyah as a source of state budget/budget. This research was conducted in Madiun by taking a sample of three villages of nine districts. The method is quantitative with ex-post facto design, collection document and questionnaire data and data product moment correlation analysis (T test). Results zero hypothesisis accepted because t0(0.059) is smaller than tt(1.96) level significansi 5% or 1% (2.59), this shows that a persons response to the zakat/jizyah as a source of state budget/budgetis proportional. Or no difference in the attitude of paying zakat/jizyah, both of whichare clear about the function of zakat, is being, or less. Respondents who understand the positive response is proportional to attitudes, respondents were then negative response is proportional to the negative attitude; respondents were not sure what it is a very negative response is proportional to the extremely negative attitude or do not pay zakat.Keywords:Â Respondents, attitudes,Â Zakat/Jizyah